2017
DOI: 10.1002/pds.4321
|View full text |Cite
|
Sign up to set email alerts
|

Media attention regarding sudden cardiac death associated with domperidone use does not affect in hospital ECG recording

Abstract: No effect of the media hype was found on the intensity of ECG monitoring in domperidone users. In the university medical centre, domperidone prescriptions were reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…Since July 2014, based on further evidence, dispensing domperidone in the Netherlands has required a prescription by a physician (College ter Beoordeling van Geneesmiddelen [Medicines Evaluation Board], 2014; Pharmacovigilance Risk Assessment Committee, 2014). As a result of both changing regulations and news coverage concerning domperidone, Dutch physicians, since, have been prescribing domperidone less often (Berger et al, 2017).…”
Section: Key Messagesmentioning
confidence: 99%
“…Since July 2014, based on further evidence, dispensing domperidone in the Netherlands has required a prescription by a physician (College ter Beoordeling van Geneesmiddelen [Medicines Evaluation Board], 2014; Pharmacovigilance Risk Assessment Committee, 2014). As a result of both changing regulations and news coverage concerning domperidone, Dutch physicians, since, have been prescribing domperidone less often (Berger et al, 2017).…”
Section: Key Messagesmentioning
confidence: 99%
“…As a result, first-line treatments are frequently not adhered to when one of the interacting agents is substituted, especially in primary care where ECG monitoring is often not feasible. In tertiary care, low adherence to guidelines result in many overridden DDI alerts by physicians [18]; and ECG monitoring is rarely performed when QT-DDI alerts are overridden [19,20]. With the increasing number of QTc-prolonging drugs, QT-DDI alerts will reduce the physician responsiveness to this particular type of alert, also known as alert fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, ECG QT interval measurements are not routinely performed in the clinic. One European study suggested that despite the media attention regarding domperidone-induced deaths, the rate of ECG measurements has not significantly changed and only 10% of patients prescribed domperidone receive ECG tests [34]. However, in our study, the rate of ECG monitoring in patients prescribed domperidone increased from 2011 to 2016.…”
Section: Discussionmentioning
confidence: 54%